2010
DOI: 10.5194/angeo-28-2127-2010
|View full text |Cite
|
Sign up to set email alerts
|

Recent progresses in relativistic beam-plasma instability theory

Abstract: Abstract. Beam-plasma instabilities are a key physical process in many astrophysical phenomena. Within the fireball model of Gamma ray bursts, they first mediate a relativistic collisionless shock before they produce upstream the turbulence needed for the Fermi acceleration process. While non-relativistic systems are usually governed by flow-aligned unstable modes, relativistic ones are likely to be dominated by normally or even obliquely propagating waves. After reviewing the basis of the theory, results rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The Weibel instability appears to be important for catalyzing shocks in unmagnetized plasmas. With the discovery of relativistic blast waves from GRB, it has received much attention, [1][2][3][4][5][6][7][8], and appears to be confirmed by simulations. The conventional wisdom is that when two oppositely directed plasma streams collide, the Weibel instability generates small-scale magnetic fields; particle scattering off these magnetic fluctuations provides an isotropization mechanism necessary for the shock transition to form.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The Weibel instability appears to be important for catalyzing shocks in unmagnetized plasmas. With the discovery of relativistic blast waves from GRB, it has received much attention, [1][2][3][4][5][6][7][8], and appears to be confirmed by simulations. The conventional wisdom is that when two oppositely directed plasma streams collide, the Weibel instability generates small-scale magnetic fields; particle scattering off these magnetic fluctuations provides an isotropization mechanism necessary for the shock transition to form.…”
Section: Introductionmentioning
confidence: 88%
“…1 With the discovery of relativistic blast waves from gamma-ray bursts, it has received much attention (Medvedev & Loeb 1999;Brainerd 2000;Wiersma & Achterberg 2004;Lyubarsky & Eichler 2006;Achterberg & Wiersma 2007;Bret 2009;Bret et al 2010;Yalinewich & Gedalin 2010;Rabinak et al 2011;Lemoine & Pelletier 2011) and appears to be confirmed by simulations. The conventional wisdom is that when two oppositely directed plasma streams collide, the Weibel instability generates small-scale magnetic fields; particle scattering off these magnetic fluctuations provides an isotropization mechanism necessary for the shock transition to form.…”
Section: Introductionmentioning
confidence: 97%
“…The plasma is not a passive medium, and there will be interaction between the electron beam and the plasma [5,6]. The interaction will lead to variety instabilities [7][8][9], and it will make the mechanism of radiation become more complex [10][11][12]. According to the physical process of the microwave radiation from the vacuum diode, this paper establishes a mathematic model of the process and obtains the dispersion relations of the model, and then the paper compares and analyzes the theoretical results and the actual measurement results of radiation.…”
Section: Introductionmentioning
confidence: 99%
“…The physics of the linear Buneman instability is fairly well understood [11] in the nonquantum ( = 0) and non-relativistic (1/c = 0) cases ( is the reduced Planck's constant and c is the speed of light in vacuum). In other situations, relatively thin beams of electrons penetrate a plasma consisting of both electrons and ions, giving rise to electron two-stream and ion Buneman instabilities in different parameter regimes in the non-relativistic [12] and relativistic [13][14][15] regimes. An electron beam propagating through a plasma can give rise to electrostatic two-stream instabilities when the wave vector and electric field are aligned, and electromagnetic instabilities obliquely to the beam direction.…”
Section: Introductionmentioning
confidence: 99%
“…In other situations, relatively thin beams of electrons penetrate a plasma consisting of both electrons and ions, giving rise to electron two-stream and ion Buneman instabilities in different parameter regimes in the nonrelativistic [12] and relativistic [13][14][15]r e g i m e s .A n electron beam propagating through a plasma can give rise to electrostatic two-stream instabilities when the wave vector and electric field are aligned, and electromagnetic instabilities obliquely to the beam direction. A typical condition for the ion motion to become important in a current-neutral plasma is γ αM/(mZ i ), with γ being the electron beam γ factor, α the beam to plasma density ratio, Z i the ion charge state, and M and m the ion and electron masses [12], respectively.…”
Section: Introductionmentioning
confidence: 99%